Qualidade de vida relacionada à saúde de pacientes com câncer em quimioterapia - Nicolussi, Adriana Cristina (2014)
It is a cross-sectional study to evaluate the health-related quality of life in cancer patients undergoing chemotherapy, to identify the domains affected and associate them with socio-demographic and clinical-therapeutic features of the sample. It was performed with 152 patients between 2009 and 2011 in two centers of chemotherapy, in Ribeirão Preto, SP, Brazil. The instrument Quality of Life Questionnaire Core-30 was used. The general Quality of Life was considered good, the domains affected were: emotional and role function, pain, fatigue, insomnia and loss of appetite. Female patients, between 40 and 60 years, economically active, with gastric, lung, neurological and skin cancer, with metastasis, and patients who under wentsurgery and/or radiotherapyshowed concomitant deficitsin several areasand the presence ofmore symptoms. We concluded that the cancer and its treatment somehow affected patients, causing more symptoms and deficits of the performed functions, jeopardizing their health-related quality of life.